To simplify the expression \( (60 \div 3 \cdot 2) - 5 + 4 \), we follow the order of operations (parentheses, exponents, multiplication and division from left to right, addition and subtraction from left to right).
-
First, perform the division: \[ 60 \div 3 = 20 \]
-
Next, multiply the result by 2: \[ 20 \cdot 2 = 40 \]
-
Now substitute back into the expression: \[ 40 - 5 + 4 \]
-
Proceed with subtraction: \[ 40 - 5 = 35 \]
-
Finally, add 4: \[ 35 + 4 = 39 \]
Thus, the simplified result is \( \boxed{39} \).